Synthesis of the aminocyclitol units of (-)-hygromycin a and methoxyhygromycin from myo-inositol - Gurale, Bharat P.; Shashidhar, Mysore S.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2012)
Concise and efficient syntheses of the aminocyclitol cores of hygromycin A (HMA) and methoxyhygromycin (MHM) have been achieved starting from readily available myo-inositol. Reductive cleavage of myo-inositol orthoformate to the corresponding 1,3-acetal, stereospecific introduction of the amino group via the azide, and resolution of a racemic cyclitol derivative as its diastereomeric mandelate esters are the key steps in the synthesis. Synthesis of the aminocyclitol core of hygromycin A involved chromatography in half of the total number of steps, and the aminocyclitol core of methoxyhygromycin involved only one chromatography.